2001
DOI: 10.1007/s00464-001-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Study comparing sutures and nonpenetrating titanium clips for arteriotomy closure after embolectomy

Abstract: The VCS clip applier system, a quick and easy method for closing arteriotomies, is as safe as sutures in terms of narrowing of the artery and formation of pseudoaneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…A clinical series examining vascular access in hemodialysis revealed that the application of VCS clips is an easy to manipulate, safe, and time‐saving method compared with hand‐sutured anastomosis . Similar results have been reported for arteriotomy closure after embolectomy, peripheral arterial bypass procedures and graft replacements . Theoretically, the vascular intima is intact, and hyperplasia is absent after achieving anastomosis with non‐penetrating clips, as demonstrated in animal experiments .…”
Section: Introductionsupporting
confidence: 53%
“…A clinical series examining vascular access in hemodialysis revealed that the application of VCS clips is an easy to manipulate, safe, and time‐saving method compared with hand‐sutured anastomosis . Similar results have been reported for arteriotomy closure after embolectomy, peripheral arterial bypass procedures and graft replacements . Theoretically, the vascular intima is intact, and hyperplasia is absent after achieving anastomosis with non‐penetrating clips, as demonstrated in animal experiments .…”
Section: Introductionsupporting
confidence: 53%
“…Pikoulis, et al, 9 published a comparative study of vascular closure staple clips and interrupted nylon sutures in surgery of upper-or lower-extremity embolisms. 9 In their study, the time required for arteriotomy closure with these clips was considerably shorter than the time required for suturing, resulting also in shorter clamp times (closure with clip compared with suture: 11.2 Ϯ 2.7 seconds compared with 241.2 Ϯ 48.7 seconds; clamp times: 380.8 Ϯ 127.3 seconds compared with 612.7 Ϯ 112.6 seconds).…”
Section: Discussionmentioning
confidence: 99%
“…30 The nonpenetrating titanium clip system permits reapproximation of vascular edges without penetrating the vessel wall. [31][32][33][34] It has demonstrated efficacy for use in major vascular injuries in skull base surgery and has recently been approved for dural reconstruction for its potential in preventing postoperative CSF leaks. 6,35 Thus far, there is evidence that the clips can be used to repair leaks in the spinal dura, [36][37][38][39] as well as one case report that demonstrated the use of titanium clips in repairing a CSF leak at the skull base.…”
Section: Discussionmentioning
confidence: 99%